Psychosocial parameters as determinants of return to work among stroke survivors - Pascal Chidera Uzoh; Adebisi I. Hammed; Ezekiel Onyemechi; Chigozie O. Obaseki; Susan O. Kubeyinje (Exercise and Quality of Life)
This study investigated the psychosocial parameters as determinants of return to work among stroke survivors. This study involved 49 stroke survivors. Hospital Anxiety and Depression Scale (HADS) was used to determine the levels of anxiety and depression of the subjects. Equally, Health-Related Quality of Life (HRQOL) of the subjects was measured with the Stroke Specific Quality of Life (SS-QOL) scale. Also, a self-structured questionnaire was used to determine return to work of the subjects. The difference between stroke survivors that returned to work and those that did not return to work was established using Pearson’s chi-squared test. Also, Independent sample t-test was used to test for significance. Statistical significance was accepted for a p-value of <0.05. The outcome of this study showed a significant (p<0.05) difference in the depression of stroke survivors that returned to work and those that did not return to work. Also, significant (p<0.05) differences exist in the anxiety and quality of life of stroke survivors that returned to work and those that did not return to work. Likewise, age was found to have a significant influence on return-to-work status (p<0.05). Besides, gender, occupation and duration of physiotherapy had no significant (p > 0.05) influence on return-to-work status of stroke survivors. This study, therefore concluded that the level of depression, anxiety, and quality of life can substantially have an influence on return to work or otherwise among stroke survivors. Therefore, health professionals should develop and incorporate strategies to enhance the quality of life, prevent depression and anxiety in the management of stroke survivors.